Dietary Rosa mosqueta (Rosa rubiginosa) oil prevents high diet-induced hepatic steatosis in mice. Issue 9 (2nd September 2015) - D'Espessailles, Amanda; Dossi, Camila G.; Espinosa, Alejandra; González-Mañán, Daniel; Tapia, Gladys S.
<x xml:space="preserve">Abstract</x> The effects of dietary Rosa mosqueta (RM, Rosa rubiginosa) oil, rich in α-linolenic acid, in the prevention of liver steatosis were studied in mice fed a high fat diet (HFD).